Penerapan Jadwal Amortisasi dan Dana Pelunasan pada Kredit Perumahan Rakyat (KPR) - Arnah Ritonga; Bobby Putra Delon Togatorop; Lestari Novianti Sinurat; Monica Triyuni Sinaga; Widya Kartini Pangaribuan (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2025)
This study aims to examine the use of amortization schedules and the repayment fund approach in Public Housing Credit. By applying quantitative descriptive methods and a case study approach, this study simulates a mortgage with a credit ceiling of Rp163,800,000, a tenor of 15 years, and an interest rate of 5.65% for the first to fifth year and 13% for the sixth to fifteenth year. The results of the simulation show that without any additional strategies, the total interest to be paid reaches Rp138,887,134.14, which is almost equivalent to the total principal loan. However, by using a sinking fund strategy through regular savings of Rp1,000,000 every month (with an interest rate of 0.25% per month) for 5 years, the collected funds are Rp64,444,800 which significantly reduces the remaining principal loan. As a result, the total interest is reduced to Rp87,864,324.85, which means there is a savings of Rp51. 022. 809.29. Furthermore, this strategy has the potential to shorten repayment time. In conclusion, sinking funds are an effective approach to reducing interest burden and accelerating the repayment of Public Housing Loans.